Apnea as an uncommon preoperative manifestation of medulla cavernous malformation: Surgical treatment and literature review. (June 2014) - Li, Da; Hao, Shu-Yu; Lou, Xiao-Hui; Tang, Jie; Xiao, Xin-Ru; Wu, Zhen; Zhang, Li-Wei; Zhang, Jun-Ting
Abstract Objective. Apnea is not a common preoperative manifestation of medulla cavernous malformations (CMs). The role of surgical resection in patients suffering from apnea secondary to hemorrhage from medulla CMs requires further definition. Methods. Medical records and radiographs were reviewed retrospectively for four patients treated surgically for medulla CMs in our institution between 2008 and 2011. Recent outcomes for these patients were also evaluated. The modified Rankin Scale (mRS) was used to evaluate neurological function. Results. All four patients (3 male, 1 female; mean age: 41.3 years) suffered two or three hemorrhages with a preoperative mRS of five and, due to the loss of autonomous respiration and consciousness, underwent a preoperative tracheotomy for mechanical ventilation, which lasted an average of 4.5 days. Prior to surgery, all patients had recovered to the point of maintaining spontaneous breath and normal blood gas values with oxygen supplementation. Lesions were totally resected in all patients via the posterior suboccipital approach. Postoperative ventilation was continued in one patient for 1 day. The mean postoperative mRS score at discharge was 3.5, and all patients had improved from their previous scores. The tracheostomy was closed in three patients at 15, 16, and 35 days after surgery. After a mean follow-up of 34.7 months, the most recent mRS scores were 3, 2, 2, and 2; no recurrent hemorrhage was noted, and three patients lived independently. Conclusion. In carefully selected patients with hemorrhage due to medulla CMs, favorable outcomes can be achieved even if apnea was a part of the preoperative clinical presentation. Surgery should be considered in these patients, particularly in those with repeated hemorrhages, and apnea should not be considered an absolute contraindication to surgery.